Chinese agricultural cooperation in sub-Saharan Africa. Challenging preconceptions - Gabas, Jean-Jacques; Tang, Xiaoyang (Perspective, 2014)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"Chinese agricultural cooperation in sub-Saharan Africa is surrounded by preconceptions: high amounts of aid, massive land grabs to feed China, an inert cooperation model, and centralised orchestration by the government. These ideas mean that certain long-standing operators in the field of cooperation with Africa mistrust or even disregard this key player. This mistrust must be overcome in the current context. Since the mid-1980s, funding for Africa’s agricultural development has been steadily declining, despite a slight upturn since the 2008 food crisis. Moreover, the cooperation models of traditional donors are being reformed, and agriculture is becoming an international priority once more. Although information is still lacking or opaque, it is important to clarify the rationale and the instruments of Chinese cooperation, and to compare viewpoints."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"Chinese agricultural cooperation in sub-Saharan Africa is surrounded by preconceptions: high amounts of aid, massive land grabs to feed China, an inert cooperation model, and centralised orchestration by the government. These ideas mean that certain long-standing operators in the field of cooperation with Africa mistrust or even disregard this key player. This mistrust must be overcome in the current context. Since the mid-1980s, funding for Africa’s agricultural development has been steadily declining, despite a slight upturn since the 2008 food crisis. Moreover, the cooperation models of traditional donors are being reformed, and agriculture is becoming an international priority once more. Although information is still lacking or opaque, it is important to clarify the rationale and the instruments of Chinese cooperation, and to compare viewpoints."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Chinese agricultural cooperation in sub-Saharan Africa is surrounded by preconceptions: high amounts of aid, massive land grabs to feed China, an inert cooperation model, and centralised orchestration by the government. These ideas mean that certain long-standing operators in the field of cooperation with Africa mistrust or even disregard this key player. This mistrust must be overcome in the current context. Since the mid-1980s, funding for Africa’s agricultural development has been steadily declining, despite a slight upturn since the 2008 food crisis. Moreover, the cooperation models of traditional donors are being reformed, and agriculture is becoming an international priority once more. Although information is still lacking or opaque, it is important to clarify the rationale and the instruments of Chinese cooperation, and to compare viewpoints.